A hurricane wind risk and loss assessment of Caribbean agriculture. (4th August 2016) - Mohan, Preeya; Strobl, Eric
Abstract: Hurricanes act as large external shocks potentially causing considerable damage to agriculture in the Caribbean. While a number of studies have estimated their historic economic impact, arguably the wider community and policy makers are more concerned about their future risk and potential losses, since this type of information is useful for disaster preparedness and mitigation strategy and policy. This paper implements a new approach to undertaking a quantitative wind risk and loss assessment of agriculture in Caribbean island economies. The authors construct an expected loss function that uses synthetically generated, and historical, hurricane tracks within a wind field model that takes cropland exposure derived from satellite data into consideration. The results indicate that expected wind losses are potentially large but vary considerably across the region, where the smaller islands are considerably more likely to be negatively impacted. Moreover, we find that the structure of the agricultural sector can be important in terms of vulnerability.